2020
DOI: 10.1016/j.scitotenv.2020.138811
|View full text |Cite
|
Sign up to set email alerts
|

A spatio-temporal analysis for exploring the effect of temperature on COVID-19 early evolution in Spain

Abstract: • No evidence of a relationship between COVID-19 cases and temperature was found. • Results should not be extrapolated to other temperature ranges. • These results should be interpreted carefully due to data uncertainty and confounders. • It is important to account for nonmeteorological, spatial and temporal effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
264
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(287 citation statements)
references
References 36 publications
19
264
1
3
Order By: Relevance
“…Shi et al (2020), by contrast, noted that temperatures over 8°–10 °C decreased the daily incidence of COVID-19 cases. Other specialists, on the other hand, namely Iqbal et al (2020) and Briz-Redón and Serrano-Aroca (2020) , found no evidence of a link between rates of COVID-19 cases and temperature in either China or Spain.…”
Section: Resultsmentioning
confidence: 92%
“…Shi et al (2020), by contrast, noted that temperatures over 8°–10 °C decreased the daily incidence of COVID-19 cases. Other specialists, on the other hand, namely Iqbal et al (2020) and Briz-Redón and Serrano-Aroca (2020) , found no evidence of a link between rates of COVID-19 cases and temperature in either China or Spain.…”
Section: Resultsmentioning
confidence: 92%
“…Yet, there is limited agreement on the shape and magnitude of those relationships. While studies find correlations between pandemic severity and variations in temperature (9,(15)(16)(17)(18)(19)(20)(21)(22), relative and absolute humidity (9,(16)(17)(18)(19)(20)(21)(22)(23)(24), ultraviolet light (19), wind speed (18,21), visibility, and precipitation (17), others (19,(25)(26)(27) indicate weaker, inconsistent, or no relationships. A recent review finds inconclusive evidence for the role of weather in COVID-19 transmission (1) and others caution against interpreting weather as a key driver due to this uncertainty (28).…”
Section: Introductionmentioning
confidence: 99%
“…Our work also contributes to the insight into the characteristics of COVID-19 cases particularly in tropical climates which are still limited in the literature [17]. It is known that most of the research on the link of weather data and COVID-19 cases available in the literature comes from sub-tropical countries [29,38,39].…”
Section: Discussionmentioning
confidence: 97%
“…average temperature (Tave), minimum temperature (Tmin), maximum temperature (Tmax) and average relative humidity (RH). Those are variables most frequently investigated in previous COVID-19 studies [19,20,29,30]. T-ave and RH were computed from hourly observations (24 data per day).…”
Section: Data and Methodsologymentioning
confidence: 99%